Analysis of the potential features in multicomponent ceramic composites based on the refractory anoxic compounds (part 2) - Цигода, Владислав Владиславович; Кириленко, Катерина Всеволодівна; Петровський, Віталій Ярославович (Technology audit and production reserves, 2016)
The physical nature of thermoelectric phenomena in ceramic composites based on refractory anoxic compounds is examined in the article as the object of research. In the current operating conditions, the disadvantages of this object are a big response time, which presented in that the produced functional devices do not sensitive to the sudden peak changes in the temperature. The study of thermoelectric properties was conducted by heating the entire sample. It was placed in the oven, increase the speed of heating which is supported within 4 deg/min with an accuracy of ± 0,2 %. The temperature of the oven was parallel controlled by platinum-platinum-rhodium thermocouple. For the first time proved that for maximum Seebeck coefficient, metallic inclusions should have an elongated cylindrical shape and volume. Percolation threshold should be about 2, and fractal dimension of the cluster should be about 2,4. Obtained values contradict the Skal’s theory and need further research. It is proved that using the effect of accumulating and storing charge during their release, it can increase conductivity without reducing thermoelectric ability of the couple, which in turn will increase the thermoelectric Q-factor. These research results can be used for the manufacture of highly efficient thermoelectric converters.